Report on the State of Preparedness of the Integrated Child Development Services Projects (July—October, 1976) - Planning Commission (Planning Commission, 1978)
At the time of sanction of the pilot ICDS Projects, PEO was requested to undertake an independent evaluation. 2. The design of the study provides for the present Report on the ‘State of Preparedness’ as after one year of operation of the scheme, for which held work was done during July-Oct. 76, and a final report also containing an assessment of the overall impact of the projects, after a repeat round in the mid-1977. 3. A great deal of effort has undoubtedly been put in for getting the ICDS Projects off the ground.
Programme Evaluation Organisation, Planning Commission, Government of India
Programme Evaluation Organisation, Planning Commission, Government of India